Ecological study of social fragmentation, poverty, and suicide. Issue 7216 (16th October 1999) - Whitley, Elise; Gunnell, David; Dorling, Daniel; Smith, George Davey
Abstract: Objectives: To investigate the association between suicide and area based measures of deprivation and social fragmentation. Design: Ecological study. Setting: 633 parliamentary constituencies of Great Britain as defined in 1991. Main outcome measures: Age and sex specific mortality rates for suicide and all other causes for 1981-92. Results: Mortality from suicide and all other causes increased with increasing Townsend deprivation score, social fragmentation score, and abstention from voting in all age and sex groups. Suicide mortality was most strongly related to social fragmentation, whereas deaths from other causes were more closely associated with Townsend score. Constituencies with absolute increases in social fragmentation and Townsend scores between 1981 and 1991 tended to have greater increases in suicide rates over the same period. The relation between change in social fragmentation and suicide was largely independent of Townsend score, whereas the association with Townsend score was generally reduced after adjustment for social fragmentation. Conclusions: Suicide rates are more strongly associated with measures of social fragmentation than with poverty at a constituency level.